Values of Struggle in The Novel Bunga Di Hari Lalu by Galih Pranata - Nuraniki Afif Utami (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This study examines the values of struggle in Galih Pranata’s novel Bunga di Hari Lalu through a sociological approach to literature. The novel not only presents the love story of Soediro and Prillie, but also portrays the social realities experienced by indigenous people in the Dutch East Indies in the early twentieth century. Soediro is depicted as an intellectual who struggles through education, literacy, and social awareness. The findings show values of resistance to discrimination, perseverance, nationalism, education as a means of struggle, and morality. These values remain relevant beyond the colonial context and may inspire the present generation in facing social and educational challenges. Bunga di Hari Lalu therefore functions not only as a literary work, but also as a historical reflection and a source of inspiration for intellectual struggle.